Effects of Paclobutrazol and Daminozide on the Growth of Acacia mangium Seedlings - Abod, Sheikh Ali; Yasin, Sulaiman (Universiti Putra Malaysia Press, 2002)
Low concentrations of paclobutrazol and daminozide at 0, 5, 10 and 15 mgt] were foliar sprayed on 12 week old A. mangium seedlings at three different frequencies of application i.e. 1 (week 0), 2 (week 0 & 4) and 3 (week 0, 4 & 6). Either chemical was effective in controlling growth but paclobutrazol was more potent than daminozide. A low concentration of 5 mgt] paclobutrazol at 1 application was sufficient to cause a significant reduction in height growth compared to daminozide which required a minimum concentration of 10 mgt] with 2 applications. In general, the main effects of the chemicals increased with increasing concentration and frequency of spray.